Batik Inspiration of Shibori Tie-dye techniques/ Lilinieta Talib, Nur Fatin Umar and Zolina Mohamad - Talib, Lilinieta; Umar, Nur Fatin; Mohamad, Zolina (Universiti Teknologi MARA, Perak, 2024)
This article presents the study of the tie and dye subject in the Fashion Design Program, College of Creative Arts and Design, UiTM Perak, Malaysia, which focuses on how the program's first-year diploma students are experimenting with exploring colours by using related tie-dye Shibori techniques with batik inspiration on fabric which can be incorporated and utilised in many ways for fashion design work. This article addressed the background of tie-dye Shibori techniques within the realm of batik inspirations, expanding the traditional understanding of the ancient Japanese art of tie-dyeing. The study aims to explore the students' experimental level of activities on techniques of tie-dye Shibori by focusing on the types of Shibori outcome techniques and the pre-and post-activity learning experience in the experiment process. The methodology mainly the Action research design involves closed observations by participatory approach, interactive process and reflective practice in which students critically show their actions and outcomes to learn from the process of tie-dye Shibori techniques. Findings of the results indicate the three tie-dye Shibori techniques that students have chosen and each of the techniques highlights the significant uniqueness and challenges in the process. This article concludes by exploring students' skills and understanding, the young fashion designers stage can prove that the subject of tie-dye Shibori has its potential. These can be seen in terms of students' perceptions towards self-appreciation in their work art performance. These various perceptions can significantly impact fashion design student's motivation, job satisfaction, and overall well-being at work after graduating from their studies and in the future sustainable community.